Acetylcholinesterase activity in the freshwater shrimp Caridina nilotica as a biomarker of Roundup(®) herbicide pollution of freshwater systems in South Africa - Mensah, P K (Water science and technology : a journal of the International Association on Water Pollution Research, 2012)
The use of Caridina nilotica whole-body acetylcholinesterase (AChE) activity as a potential biomarker of Roundup(®) pollution of aquatic ecosystems was investigated. Forty days post hatch (dph) shrimps were exposed to different concentrations of 0.0, 4.3, 6.7, 10.5, 16.4, 25.6 and 40.0 mg/L in a 96 h acute toxicity test; and 0.0, 2.2, 2.8, 3.4, 4.3 and 5.4 mg/L in a 21 d chronic toxicity test. Whole-body AChE activities were determined at the end of the exposure periods by spectrophotometric assay of sample extract; activities were then normalized against protein contents in the samples and expressed in nanomoles of substrate hydrolyzed. Results of both tests showed that AChE activity was concentration-dependent. Mean AChE activities and standard deviations (±SD) for 96 h acute toxicity were 3.6239 (± 0.4185), 3.4157 (± 1.1842), 2.537 (± 1.3989), 2.4253 (± 1.4202), 2.4127 (± 1.9097), 2.0017 (± 1.1080) and 2.316 (± 0.4001) nmol/min/mg protein; while activity levels for 21 d test were 3.6907(± 0.3401), 2.8473 (± 0.713), 2.9134 (± 0.9879), 2.6738 (± 0.7117), 2.3019 (± 0.4464) and 2.1478 (± 0.864) nmol/min/mg protein. Reference basal AChE activity for 40 dph C. nilotica based on the two control groups was estimated as 3.6907 (± 0.3401) nmol/min/mg proteins. The present work provides ecotoxicological basis for the possible use of AChE activity in C. nilotica as a biomarker for monitoring Roundup(®) pollution in freshwater systems